Gesellschaftlicher Aufbruch, reale Utopien und die Arbeit am Sozialen - Böhnisch, Lothar (bu,press, 2013)
People around the world recollect socially responsible and desirable values, new forms of living and coexistence as well as eco-social economic activities. This volume is dedicated to these real utopias -positive ideas aiming at a better future and practical approaches combining notions of a more livable society with concrete practical implementations.